Coping with Curriculum Change in South Africa. Issue 1 (1st December 2000) - St Clair Dean, Jacqueline
The paper looks at managing change through a teacher/adviser development programme in South Africa. Programme teachers and advisers are working within the context of an unequal, divided history and recent education initiatives which require all educators to move from a rigid, authoritarian model of education to one radically different, based on outcomes. Participants in the programme experience alternative models of education in the UK and subsequently in South Africa, in particular Nuffield history approaches. This has helped them to develop new ways of thinking and a range of skills and understandings rooted in new experiences, new knowledge and participant research. Crucially, the programme promotes democracy within its structures and philosophy, addressing teacher/adviser autonomy and professionalism through action research and reflective practice. The paper charts changes in participants' orientation, beliefs and practice. Professional development is evidenced through programme members' reflections on their experiences and practice. Some key obstacles to change and equity are discussed.